The Smart Saving Movement: Enhancing the Financial Independence of PKK Women in Bantaragung Village, Majalengka, West Java - Depi Hasanah; Muniroh; Ifah Masrifah; Fera Lufhidarani Pranita; Rianto (Britain International for Academic Research (BIAR) Publisher, 2026)
Household financial management is often a challenge for homemakers in rural areas, where limited financial literacy hinders the achievement of financial independence. The lack of separation between funds for daily expenses and reserve funds (savings) underscores the urgent need for structured financial education programs. This community service activity aims to improve understanding of household budget management and the culture of saving in order to support the financial independence of the women of the PKK in Bantaragung Village, Majalengka Regency, West Java. The PKM was implemented through outreach, training in household financial management, and guidance on the culture of saving for the women of the Bantaragung PKK. The participants in this study were PKK members selected using purposive sampling. The results of the program showed an increase in the participants’ understanding and awareness of the importance of setting aside income first (“saving first”) before using it for consumption needs. Through this mentoring, the PKK women were able to apply a priority-based cash management strategy and began utilizing safer and more structured savings products. . This program encourages participants to begin adopting more systematic financial management practices by setting aside a portion of their income for savings and tracking daily expenses using the Excel spreadsheet we provide. The Smart Savings Movement has proven effective as a tool for strengthening the domestic economy. Synergy between financial literacy education and social organizations such as the PKK is key to achieving sustainable family economic resilience at the village level.s